Comparative study of the morphology and properties of PP/LLDPE/wood powder and MAPP/LLDPE/wood powder polymer blend composites (eXPRESS Polymer Letters)
In this study, polypropylene (PP)/linear low-density polyethylene (LLDPE) and maleic anhydride grafted polypropylene (MAPP)/LLDPE blend systems were comparatively investigated. The blends and composites contained equal amounts of the two polymers, and the compatibility and miscibility between the two polymers were investigated. Composites with 10, 20 and 30 wt% wood powder (WP), but still with equal amounts of the two polymers, were prepared and investigated. The morphologies, as well as mechanical and thermal properties, of the blends and the blend composites were investigated. The MAPP/LLDPE blend and composites showed better properties than the PP/LLDPE blend and composites as a result of the stronger interfacial interaction between MAPP, LLDPE and WP. The SEM and DSC results of the PP/LLDPE/WP blend composites showed that WP located itself more in the LLDPE phase. In the MAPP/LLDPE/WP composites the WP was in contact with both polymers, although it had a greater affinity for MAPP. The TGA results show that the MAPP/LLDPE blend and composites are more thermally stable than the PP/LLDPE blend and composites.